Avaliação da precisão planialtimétrica de métodos pós-processados e pré-processados - Ataide, João Vitor Alencar Rosa (Universidade Federal Rural do Semi-Árido, 2019)
Topography is increasingly advancing its techniques, survey methods that differ in accuracy and speeds in obtaining information for execution of projects, mainly in the areas of civil engineering and surveying. Thus, it is necessary to evaluate which method has the greatest precision, the shortest execution time, and the higher quality in obtaining the data. The most common methods of surveying are the Preprocessed and Postprocessed methods, where they differ in the need for correction and georeferencing of the surveys, but their applicability can be the same in the planimetry or altimetry. Thus, it aims to evaluate the accuracy of the planialtimetric methods of cartographic production, comparing the products quantitatively and qualitatively. For this, topographic equipment was used: Total Station, GPS-Static, GPS-RTK, as well as software Qgis 2.18, used to create the products of the thematic charts, in addition to using the Cartographic Accuracy Standard Products Digital Cartography (CASPDC) and Root Mean Square Error (RMSE) to compare accuracy of cartography of surveys. The products obtained by the data from the surveys are classified as "Class A", which is the most accurate according to CAS-PDC. As a result of the processing, the following products were obtained: Digital Elevation Model (DEM), contour lines, three-dimensional DEM (DEM-3D), drainage networks. Finally, it can be concluded that the difference between the survey methods used is low, since the RMSE was 1.6 cm for altimetry and 36 cm for planimetry, while the difference between the forms of the contour curves is related to the amount of collected points or sample density such as the grid mesh arrangement. In this way, the RTK survey becomes more convenient in data collection and data efficiency, and also has great accuracy.
Keywords: Cartografia; Curvas de nível; Raiz do erro médio quadrático; Padrão de exatidão cartográfico; Modelo digital de elevação; Cartography; Level curves; Root mean square error; Cartographic accuracy pattern; Digital elevation model; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA